High SARS-CoV-2 Infection Rates Among Special Forces Police Units During the Early Phase of the COVID-19 Pandemic in Ecuador - Ortiz-Prado, Esteban; Andrade, Felipe; Vasconez, Eduardo; Escobar-Espinosa, Cristina; Vallejo-Janeta, Alexander Paolo; Freire-Paspuel, Byron; Coronel, Barbara; Galvis, Heberson; Morales-Jadan, Diana; Rivera-Olivero, Ismar A.; Lozada, Tannya; Henriquez-Trujillo, Aquiles R.; et al. (Frontiers in Medicine, 2022)
Background At the beginning of the COVID-19 pandemic, health workers and first-responders, such as police officers, were in charge of trying to contain a disease that was unknown at that time. The lack of information and the tremendous need to contain new outbreaks put police officers at higher risk. Methodology A cross-sectional study was conducted to describe SARS-CoV-2 infection rates among Police Special Forces Officers in Quito, Ecuador. In this study, 163 community-dwelling police officers from elite divisions voluntarily participated in our SARS-CoV-2 detection program using reverse transcription quantitative real-time PCR (RT-qPCR). Results A total of 20 out of 163 police officers tested positive for SARS-CoV-2, yielding an infection rate of 12.3%. Within this cohort, 10% (2/20) of SARS-CoV-2 positive individuals were potentially super spreaders with viral loads over 108 copies/ul. About 85% of the SARS-CoV-2 positive individuals were asymptomatic and 15% reported mild symptoms related to COVID-19. Conclusions We found a high SARS-CoV-2 infection rate within the special forces police officers that, beyond a high health risk for themselves, their families, and coworkers. Our results point out the need for permanent SARS-CoV-2 testing among asymptomatic essential workers and first-responders to avoid local outbreaks and to prevent work-place absenteeism among police special units.